Transgenesis in the parasitic nematode Strongyloides ratti - Li, Xinshe; Shao, Hongguang; Junio, Ariel; Nolan, Thomas J.; Massey, Holman C.; Pearce, Edward J.; Viney, Mark E.; Lok, James B. (Molecular and biochemical parasitology, 2011)
Strongyloides ratti can be transformed by gonadal microinjection of DNA constructs. This parasite is advantageous for derivation of stable transgenic lines because of its well-adapted laboratory host. [Display omitted] •Strongyloides ratti can be transformed by gonadal microinjection of DNA constructs. • Constructs with regulatory sequences from Strongyloides stercoralis are expressed in S. ratti. • Transformation frequencies and expression patterns in the two are highly similar. •S. ratti has major advantages over S. stercoralis in derivation of transgenic lines. Strongyloides and related genera are advantageous subjects for transgenesis in parasitic nematodes, primarily by gonadal microinjection as has been used with Caenorhabditis elegans. Transgenesis has been achieved in Strongyloides stercoralis and in Parastrongyloides trichosuri, but both of these lack well-adapted, conventional laboratory hosts in which to derive transgenic lines. By contrast, Strongyloides ratti develops in laboratory rats with high efficiency and offers the added advantages of robust genomic and transcriptomic databases and substantial volumes of genetic, developmental and immunological data. Therefore, we evaluated methodology for transgenesis in S. stercoralis as a means of transforming S. ratti. S. stercoralis-based GFP reporter constructs were expressed in a proportion of F1 transgenic S. ratti following gonadal microinjection into parental free-living females. Frequencies of transgene expression in S. ratti, ranged from 3.7% for pAJ09 to 6.8% for pAJ20; respective frequencies for these constructs in S. stercoralis were 5.6% and 33.5%. Anatomical patterns of transgene expression were virtually identical in S. ratti and S. stercoralis. This is the first report of transgenesis in S. ratti, an important model organism for biological investigations of parasitic nematodes. Availability of the rat as a well-adapted laboratory host will facilitate derivation of transgenic lines of this parasite.